Project based learning in teaching translation: Effect on students’ performance - Retnaningsih, Woro (Journal of Educational Management and Instruction (JEMIN), 2023)
The debate among researchers regarding the best method for teaching translation remains ongoing. With various approaches available, it is crucial to empirically assess their effectiveness in different educational settings. Therefore, this study aims to address the lack of empirical evidence regarding the effectiveness of Project Based Learning (PjBL) in teaching translation. The research involved thirty-five Indonesian EFL students enrolled in the Translation Entrepreneurship course at UIN Raden Mas Said Surakarta, Indonesia. Classroom action research was conducted over eight meetings and two cycles. Pre-test and post-test data from cycle 1 and cycle 2 were analyzed using paired sample t-test in SPSS. The results indicated a significant improvement in students' translation performance (p-value 0.000 < 0.05) after using the PjBL method. In conclusion, this study demonstrated that PjBL effectively enhances students' translation skills, offering valuable insights for teachers and educational institutions to consider it as an alternative method for teaching translation.